Espalhamento coulombiano relativístico próximo das condições de simetria de spin e pseudospin - Garcia, Marcelo Gonçalves [UNESP] (2015)
The relativistic scattering of spin-0 bosons and spin-1/2 fermions by spherically symmetric Coulomb potentials is analyzed in detail with an arbitrary mixing of vector and scalar couplings. It is shown that the partial wave series for both bosons and fermions reduces the scattering amplitude to that one resulting in the Rutherford formula exactly when the vector and scalar potentials have the same magnitude. The same happen in the approximation for weak potentials. The behavior of the scattering amplitude near the conditions that furnish its closed form is also discussed. From the complex poles of the partial scattering amplitude for bosons the exact closed form of bound-state solutions for both particles and antiparticles with different scenarios for the coupling constants are obtained. Perturbative breaking of the accidental degeneracy appearing in a pair of special cases is related to the nonconservation of the Runge-Lenz vector. In the case of fermions, the closed form for the partial wave series occurs not only for the spin and pseudospin symmetries but also when there is a slight breaking of the same. It is shown that in the non-relativistic limit, the differential cross section obtained reduces to Rutherford's cross section when there are spin and pseudospin symmetries and to Mott differential cross section when the symmetry is slightly broken